Ngopi Bareng Ilmu: Kolaborasi Mahasiswa dengan Masyarakat untuk Edukasi Berkelanjutan melalui Kegiatan Pengabdian Kepada Masyarakat - Arinita, Rafina; Putri, Fitriani Sagita; Andini, Egi; Pratama, Aldy Arya (Universitas Pamulang, 2025)
Community service is one of the implementations of the Tri Dharma of Higher Education, aimed at making a real contribution to society. This activity is based on the importance of sustainable education to support the development of micro, small, and medium enterprises (MSMEs). The partner in this activity is the manager of Likely Cafe, a local culinary business facing challenges in creating a sustainable business strategy. The purpose of this program is to provide education through interactive discussions on business management strategies, product innovation, and digital marketing. The method used is a participatory approach through informal discussions and direct case studies. The results show that collaboration between students and business actors improves the partner’s understanding of adaptive business strategies. This activity also provides applicable learning experiences for students. In conclusion, sustainable education is proven to be an effective approach in empowering MSMEs. It is suggested that similar programs be continued regularly with wider community involvement. Keywords: community service; MSMEs; collaboration; sustainable education; business strategy